PERENCANAAN DESAIN CASING PEMBORAN DI SUMUR BH-01 LAPANGAN R - Eko Prastio; Abdullah Rizky Agusman; Bagus Hery Refangga (Jurnal Bhara Petro Energi, 2026)
Casing design planning is an important stage in oil and gas drilling activities that aims to maintain the stability of the drill hole, protect the formation, and ensure the safety of drilling operations. This research was conducted at the BH-01 Well of Field R with the aim of designing a safe and efficient casing configuration based on geological conditions and formation pressure. The method used is the Maximum Load Method, an analysis method that considers three main types of loads on the casing, namely burst, collapse, and tension loads. The calculation results show that the 13-3/8 inch intermediate casing with K-55 material has a safety factor value of 1.4 for burst, 1.2 for collapse, and 3.6 for tension. All of these values ​​​​exceed the minimum standards of API 5C3 and API 5CT, so it can be concluded that the casing design is safe for all types of operational loads. Thus, the casing design planning at the BH-01 well has met the technical and safety criteria, and can be used as a reference in drilling in fields with similar geological conditions.